O roteiro cinematográfico na escola: uma proposta de ensino e aprendizagem - Mota, Millena Ariella dos Santos (2018)
The cinematographic script is a discursive genre belonging to the cinematographic sphere. Because it is the written form of an audiovisual project, for many writers and producers, this genre is something temporary, that lasts only the time it takes to be transformed into the final product. However, this genre transcends this fleeting character by enabling a critical, creative and original work with writing and reading. Through it, subjects can express their world view in order to criticize and transform it; can develop innovative ideas capable of arousing interest in the other; can express themselves in an authentic and independent way without limiting their inventiveness, they can manipulate different semioses (literature, theater, dance, music, photography) and digital resources, and can, above all, write with pleasure. Through the cinematographic script, the subjects engage in a unique discursive context, interact, confront and transform themselves. Thus, the present research aims to demonstrate that the discursive genre cinematographic script can serve as a valuable tool in the teaching and learning of the Portuguese Language. This research is qualitative, since the actions are observed and analyzed in their natural environment of realization, and also applied, since it is intended to be used to solve real problems. This study focuses its analysis in two dimensions: 1) the appropriation of the constellated genres in the production of the cinematographic script and 2) in the teaching practice. The results indicate that the intervention was relevant to the development of the language skills of the students and to transformations in the teaching profession. As a theoretical contribution, Bakhtin (1997), Marcuschi (2008) and Biasi (2008) were chosen to deal with the discursive genres; to talk about the constellation of genres, Swales (2004) and Araújo (2006, 2009); to discuss multimodality, Kress and van Leeuwen (2006) and Dionisio (2008, 2014); to address the narrative sequence, Adam (1992); and to present the cinematographic script, Comparato (2000), Field (2001) and Campos (2007).